2020
DOI: 10.2174/0929867325666180719145819
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Compounds & Oxidative Stress Induced Apoptosis in Cancer Therapy

Abstract: Elevated Reactive Oxygen Species (ROS) generated by the conventional cancer therapies and the endogenous production of ROS have been observed in various types of cancers. In contrast to the harmful effects of oxidative stress in different pathologies other than cancer, ROS can speed anti-tumorigenic signaling and cause apoptosis of tumor cells via oxidative stress as demonstrated in several studies. The primary actions of antioxidants in cells are to provide a redox balance between reduction-oxidation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…Therefore, science faces the need to determine the cases-depending on the type of cells involved-in which therapeutic strategy should be used. This could represent proapoptotic effects, in the case of cancer [155,156], or antiapoptotic effects, for example, in the protection against neurodegenerative disorders [157]. Given the possibility of the modification of cell phospholipid metabolisms by exogenous compounds, there are real possibilities of modulating the cell death process, depending on the needs of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, science faces the need to determine the cases-depending on the type of cells involved-in which therapeutic strategy should be used. This could represent proapoptotic effects, in the case of cancer [155,156], or antiapoptotic effects, for example, in the protection against neurodegenerative disorders [157]. Given the possibility of the modification of cell phospholipid metabolisms by exogenous compounds, there are real possibilities of modulating the cell death process, depending on the needs of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the oxidative stress would be aggravated by the continuous generated ROS stimulated by exogenous and endogenous factors, which will induce apoptosis and necrosis once the ROS levels exceed the tolerance of tumor cells. However, due to the relatively lower ROS basic level, such situation usually does not appear in normal cells 1012. Therefore, regulating intracellular ROS signal to selectively kill tumor cells without affecting normal cells can be an effective strategy for tumor therapy 13.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNA-346 is induced under ER stress, and it is involved in autophagy/mitophagy activation to facilitate cell survival [191]. In fact, an increase of ROS during ER stress can be harmful to cancer cells [192]. In this scenario, miRNA-346 promoted mitophagy activation via GSK3 β and reduced ROS preserving cell viability [191].…”
Section: Mitophagy and Rosmentioning
confidence: 99%